Modulus of Elasticity of Two Ceramic Materials and Stress-Inducing Mechanical Deformation following Fabrication Techniques and Adhesive Cementation Procedures of a Dental Ceramic - Isgrò, G.; Rodi, D.; Sachs, A.; Hashimoto, M. (International Journal of Biomaterials, 2019)
Statement of Problem. Fabrication technique, precementation, and cementation operative procedures can induce significant modification of the stressing patterns throughout the thickness of some classes of dental ceramic materials. Objectives. To estimate, by means of the deflection test, residual stress in restorative dental ceramic following fabrication technique, precementation, and resin cement coating procedures and to relate it to the elastic property of the ceramic material tested. Materials and Methods. From IPS e.max® Press, lithium disilicate heat-pressed glass-ceramic (elastic modulus of 95 ± 5 GPa) disc-shaped specimens (n = 10) were made according to the manufacturer’s instructions. One surface of the specimens was polished to provide accurate baseline profilometric measurements (reference surface). Deflection measurements were performed after polishing and annealing alumina air-particle abrasion of the unpolished surface followed by resin cement coating of the alumina air-particle abraded surface. The specimens were reprofiled at 24, 48, and 168 hrs after coating. The Friedman test followed by Dunn’s multiple comparison test was employed to identify significant differences (p<0.05). To compare the difference in mean of maximum mechanical deflection, after cement coating at 0 hr, between two different ceramic materials (IPS e.max Press and Vitadur Alpha (result from another study)), Student’s t-test for unpaired data was performed. Results. Baseline profilometric measurements identified a convex form on the polished surface of the ceramic discs with a mean of maximum mechanical deflection of 4.45 ± 0.87 μm. A significant reduction in convexity of the polished specimens was characterized after alumina air-particle abrasion of the unpolished surface. The mean deflection significantly increased after resin cement coating and did not change over the time investigated. Conclusions. The precementation treatment, namely, alumina air-particle abrasion and cementation procedure of IPS e.max® Press glass-ceramic disc-shaped specimens generates stress that induced mechanical deformation. However, a dental ceramic material with higher elastic modulus (stiffer) would minimize stress-inducing mechanical deformation.